An Enjoyable Workplace Combined Exercise Program for Health Promotion in Trained Employees: Yoga, Pilates, and Circuit Strength Training - Konstantina Karatrantou; Christos Batatolis; Petros Chatzigiannis; Theodora Vasilopoulou; Anastasia Melissopoulou; Panagiotis Ioakimidis; Vassilis Gerodimos (MDPI AG, 2023)
Corporate wellness has become an important public health priority through the designing and implementation of different workplace exercise interventions. The objectives of this study were to investigate: (a) the effectiveness of a 4-month workplace combined yoga, Pilates, and circuit strength training program (outside work shift) on health indices, functional capacity, and physical fitness in office employees; and (b) the employees' enjoyment following the program. Fifty physically active office employees (26-55 years old) were equally divided into training (TG) and control groups (CG). The TG followed a 4-month (3 times/week, 50-60 min/training) combined yoga, Pilates, and circuit strength training program. Health indices (body composition, body mass, circumferences, musculoskeletal pains), functional capacity (flexibility, balance), and physical fitness (strength, aerobic capacity) were measured before and after the 4-month time period. After the completion of the program, the TG participants' enjoyment was assessed. The TG significantly improved (p < 0.001) all health, functional capacity (11.3-82.0%), and physical fitness indices (33.9%), except for aerobic capacity, which did not change (p > 0.05). Furthermore, a great percentage of employees (84%) reported high levels of enjoyment. This program could be effectively and safely used in workplace settings as an enjoyable intervention to improve specific health, functional capacity, and physical fitness indices in office employees.